Analisis Implementasi Kebijakan Online System Pajak Restoran dalam Meningkatkan Penerimaan Pajak Daerah pada Badan Pajak Dan Retribusi Daerah (BPRD) Jakarta Selatan - Achmad Fauzi; Dian Wahyudin (Jurnal Ilmu Administrasi Publik, 2021)
The phenomenon in this study is about the implementation of the restaurant tax system policy, where the installation of online tools at restaurants in the South Jakarta area. The purpose of this study is to analyze the implementation of the Restaurant Tax Online System policy in increasing Local Tax revenue at the South Jakarta Regional Tax and Retribution Agency (BPRD), along with the obstacles and efforts made by the Jakarta Regional Tax and Retribution Agency (BPRD) in implementing the online system policyrestaurant tax. This research uses descriptive research with a qualitative approach, namely interviews, observation and documentation. The results of this study are the implementation of the Restaurant Tax Online System Policy in Increasing Local Taxes at the Regional Tax and Retribution Agency (BPRD) of South Jakarta has been running quite well and has been implemented in accordance with the Regulation of the Governor of DKI Jakarta. In the event that the communication has carried out its duties by means of an invitation letter for socialization, the installation of online tools has increased the list of taxpayers installed. Human resources and budget that are in accordance with standards but still not maximal, commitments between management have been implemented but have not been as expected. The obstacle is that they often experience difficulties in installing online tools because taxpayers are not present or at the restaurant to be installed, human resources are still limited in IT terms. Efforts are to provide a letter of warning or warning to taxpayers in accordance with the provisions of the governor's regulation and to increase the capacity of human resources, especially regarding IT matters. His advice is to conduct regular outreach so that taxpayers comply with and understand the importance of timely tax reporting and improve human resources by participating in activities regarding the online tax system and always taxpayers through regular monitoring of the tax system and obligations for those who violate the policy.